Ameloblastomatous calcifying cystic odontogenic tumor: A review of a rare lesion - Aastha Manchanda; Seema Patil (Wolters Kluwer Medknow Publications, 2019)
Calcifying cystic odontogenic tumor (CCOT) is an uncommon developmental lesion accounting for less than 2% of odontogenic tumors. Because of its diverse histopathology, there has always been confusion about its nature as a cyst or a neoplasm, although it is well known that this lesion often occurs in association with other odontogenic tumors such as complex odontoma and ameloblastoma. It is noted that if CCOT is associated with an ameloblastoma, its behavior and prognosis will be that of an ameloblastoma, not of a CCOT. This article presents a review of all reported cases of ameloblastomatous CCOT in the last 15 years in journals indexed with PubMed.